The Role of Tourism Msmes in Local Economic Development: Systematical Literature Review - Iftita Rahmi Efendi (Jurnal Kewirausahaan dan Bisnis, 2026)
Micro, Small, and Medium Enterprises (MSMEs) in the tourism sector have a strategic role in local economic development, especially in developing countries and community-based tourism destinations. This study aims to systematically review scientific literature related to the contribution of tourism MSMEs to local economic development in the period 2013 to 2025. Using the Systematic Literature Review (SLR) approach referring to the PRISMA guidelines, 38 selected scientific articles were critically analyzed to explore research trends, key findings, study gaps, and future policy directions. The results of the analysis show that tourism MSMEs not only provide direct economic impacts, such as job creation and increasing regional income, but also contribute to cultural preservation, community empowerment, and post-pandemic destination regeneration. Recent studies emphasize the importance of local entrepreneurial ecosystems, digitalization, and social capital as determining factors for the success of MSMEs. The literature also underlines the paradigm shift towards regenerative tourism that positions MSMEs as the main actors in sustainable development. This study recommends the need for synergy between public policy, community assistance, and technological innovation to strengthen the competitiveness of tourism MSMEs in an inclusive and resilient manner. This study is expected to be an academic and practical reference in supporting the formulation of local economic development strategies that are oriented towards sustainability and social justice.Keywords: Economic, MSMEs, Tourism